Pragmatic clinical trial design in emergency medicine: Study considerations and design types. (22nd May 2022) - Gettel, Cameron J.; Yiadom, Maame Yaa A. B.; Bernstein, Steven L.; Grudzen, Corita R.; Nath, Bidisha; Li, Fan; Hwang, Ula; Hess, Erik P.; Melnick, Edward R.
Abstract: Pragmatic clinical trials (PCTs) focus on correlation between treatment and outcomes in real‐world clinical practice, yet a guide highlighting key study considerations and design types for emergency medicine investigators pursuing this important study type is not available. Investigators conducting emergency department (ED)‐based PCTs face multiple decisions within the planning phase to ensure robust and meaningful study findings. The PRagmatic Explanatory Continuum Indicator Summary 2 (PRECIS‐2) tool allows trialists to consider both pragmatic and explanatory components across nine domains, shaping the trial design to the purpose intended by the investigators. Aside from the PRECIS‐2 tool domains, ED‐based investigators conducting PCTs should also consider randomization techniques, human subjects concerns, and integration of trial components within the electronic health record. The authors additionally highlight the advantages, disadvantages, and rationale for the use of four common randomized study design types to be considered in PCTs: parallel, crossover, factorial, and stepped‐wedge. With increasing emphasis on the conduct of PCTs, emergency medicine investigators will benefit from a rigorous approach to clinical trial design.